Ministers and exiled judges in Andalusia from the Islamic conquest until the end of the era of the states of the sects (92-484 AH / 711-1091 CE - Mezher Askar, Haidar; Musa Ali, Marwa (Journal of College of Education, 2020)
As a result of the events that took place in Andalusia intensified conflicts over power and increased numbers of opponents and the multiplicity of problems became denial of the penalty of legitimacy derived from the Koran and Sunna and the consensus of Muslim scholars to a means in the hands of the Authority to punish the opponents for various reasons may deny the person to exit from the obedience of the state or the cause of the complaint or The envy of all those who oppose the authority or those who work in its institutions are ministers, judges, writers or those who do not work in the institutions of the state. Amir or the Caliph does not hesitate to deny all those who pose a threat to his power from afar or near, and this reflects the nature of the political situation at the time , The exile penalty formed a positive shift The evolution of the punishment of torture of the body to try to dimensions of the opposition or the guilty of the social field Almtlv with him and associated with the family and the family by trying to exhaust him psychologically and physically and disassociate socially.